The Influence of Entrepreneurship Education, Government Policy, and Social Support on Business Success in the Consumption Sector MSME in DKI Jakarta - Taufik Irwansyah; Agus Wibowo; Karuniana Dianta A. S (Review of Human Resources, Organizational Change, and Economic Impact, 2025)
This study aims to evaluate the effect of entrepreneurship education, government policy, and social support on business success in MSMEs in the consumption sector in DKI Jakarta. Primary data was obtained using a proportionate stratified random sampling method with a sample size of 203 MSMEs in the consumption sector in DKI Jakarta, collected through an independent survey with an online questionnaire. This research was conducted using a quantitative descriptive method, employing the Structural Equation Model Partial Least Square (PLS-SEM) technique with the SmartPLS application for data analysis.The results indicate a positive and significant effect of entrepreneurship education, government policies, and social support on business success in MSMEs. This study is limited to the scope of the DKI Jakarta area and focuses on a restricted set of variables: entrepreneurship education, government policies, social support, and business success.Entrepreneurship education equips business actors with the ability to plan, operate, and manage businesses effectively, develop new services to enhance competitiveness, and build motivation and confidence in facing business challenges. Government policies provide legal protection, ease of licensing, and tax incentives to support business sustainability. Policies such as People's Business Credit (KUR), community-based training, and support in the form of promoting local products to international markets help MSMEs expand their market reach. Social support from family, friends, or the local community assists MSME actors in expanding business networks and fostering collaboration.